2012
DOI: 10.1155/2012/142850
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of a Free Floating Vertical Axisymmetric Oscillating Water Column Device

Abstract: This paper aims at presenting a general formulation of the hydrodynamic problem of a floating or restrained oscillating water column device. Three types of first-order boundary value problems are investigated in order to calculate the velocity potential of the flow field around the device. The horizontal and vertical exciting wave forces, the rolling moment, the hydrodynamic parameters, the volume flows, and the drift forces are obtained in order to find the loads on the structure. The efficiency rate of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Note here that I m is unbounded as r → ∞, while K m is unbounded as r → 0 [22]. Hence, in view of the range of radial direction r in the sub-domain (2), both I m and K m should be included in the expression for the complex amplitude ψ 2 (see also [23]). The above expression also satisfies the boundary conditions at the two vertical plates (i.e.…”
Section: Wave Scattering Problemmentioning
confidence: 99%
“…Note here that I m is unbounded as r → ∞, while K m is unbounded as r → 0 [22]. Hence, in view of the range of radial direction r in the sub-domain (2), both I m and K m should be included in the expression for the complex amplitude ψ 2 (see also [23]). The above expression also satisfies the boundary conditions at the two vertical plates (i.e.…”
Section: Wave Scattering Problemmentioning
confidence: 99%
“…This is the case of a two-dimensional OWC with vertical thin walls [132], a vertical thin-walled circular cylindrical OWC [133] and a circular cylindrical OWC at the tip of a breakwater [134] or the tip of a coastal corner [135]. More complex geometries include a floating vertical axisymmetric OWC [136] and a twodimensional dual-chamber OWC on stepped bottom [137]. For non-diffracting OWC structures, analytical solutions can be derived from the expressions for the wave field induced by time-harmonic surface pressure distributions [124].…”
Section: Theoretical Hydrodynamic Modellingmentioning
confidence: 99%
“…Compared with the previous two OWC devices, another radiated wave field is generated by the heaving motion of the system. The correction of the optimization of turbine characteristics presented by Mavrakos & Konispoliatis (2012) has been given. It is found that the maximum extraction efficiency, under the corrected optimization of turbine characteristics, can be the same as that where a circular OWC device with thin walls is fixed in waves.…”
Section: Discussionmentioning
confidence: 99%
“…For harnessing wave energy in deeper water, a floating OWC device with a circular pontoon, which is connected to sea bed by a mooring system attached by a linear power takeoff (PTO) system, is proposed as well. Compared to the free floating OWC device by Mavrakos & Konispoliatis (2012), the integrated mooring system is beneficial to control the phase difference between the wave motion inside the air chamber and the motion of the pontoon and improve the efficiency of the floating OWC system.…”
Section: Oscillating Floating Bodymentioning
confidence: 99%
See 1 more Smart Citation